If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = 5x + 3(2x + 11) Reorder the terms: 28 = 5x + 3(11 + 2x) 28 = 5x + (11 * 3 + 2x * 3) 28 = 5x + (33 + 6x) Reorder the terms: 28 = 33 + 5x + 6x Combine like terms: 5x + 6x = 11x 28 = 33 + 11x Solving 28 = 33 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 28 + -11x = 33 + 11x + -11x Combine like terms: 11x + -11x = 0 28 + -11x = 33 + 0 28 + -11x = 33 Add '-28' to each side of the equation. 28 + -28 + -11x = 33 + -28 Combine like terms: 28 + -28 = 0 0 + -11x = 33 + -28 -11x = 33 + -28 Combine like terms: 33 + -28 = 5 -11x = 5 Divide each side by '-11'. x = -0.4545454545 Simplifying x = -0.4545454545
| (2xh)+(2xh)+(h+h)=180 | | 16x+9=15x-4 | | (X+7)(3x+5)=0 | | 3(4x-3.2)=5x-9.6 | | 3(2-3x)=52 | | 2x-4+3x=7x-3 | | 70x+90=90 | | 7x-5=5x-6 | | x^2-6x=22 | | 6u-9+3(2u+3)=4(u+3) | | 4(x+1.78)=3x | | 8n+16=8 | | 200x-0.08=600x+0.52 | | 3x+7=-2x+27 | | 6-6x=6x-10x+10 | | 3.9x-73=2.4x+5 | | 8z-24=6+2z | | 5m-7=10+3m | | 6.2=8x+1.4 | | 6-6x=6x-10+10 | | 6n-2=1 | | -4(v-4)=-7+37 | | 2y-8+14=-6 | | 2t-7=-16+t | | 3+3u=6 | | -19=5(u-5)-8u | | -3x^3+3x^2-21x+7=0 | | p-24=-19 | | 4+x-6=6x+3x+2 | | 4x-13.2=x | | 2.4x-8.6=10.6 | | -5+2u=-13 |